Education Policy and Reform in China - Zhou, Guangli; Zhou, Xiang (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book examines educational development and reform in contemporary China and focuses on some of the major issues facing education in both rural and urban areas, across the spectrum of primary, secondary, higher, adult and vocational educational pathways. The book reflects on Chinese educational strategies at a time of rapid development of the market economy and the need to promote the modernization of education. It also considers how social reform and educational changes go hand in hand and discusses the right to education irrespective of gender, nationality, particularly examining the case of children from migrant families. From the rapid development of preschool and compulsory education to the modernization of the university system, this book highlights China's ambition to create a top tier education system, fostering talent to match its requirements in a fast moving employment market and knowledge economy. .